Catchment-scale life cycle impacts of green infrastructures and sensitivity to runoff coefficient with stormwater modelling - Tang, Sijie; Yan, Xiao; Jiang, Jiping; Zheng, Yi; Yang, Yang; Xu, Peng; Shang, Fangze (The Science of the total environment, 2023)
Urban green infrastructure (GI) has been widely used in sponge city construction to manage hydrological processes. While studies on environmental benefits of GI from the perspective of whole life cycle assessment (LCA) have been reported in recent years, few have explored and compared the environmental performance of different GIs within a single catchment, which is directly linked to catchment-scale hydrological control. This study focuses on a Sponge City pilot project in Shenzhen, China, including three typical types of GI: permeable pavement, green roof, and sunken green space. By collecting hydrological data, land use, and life cycle inventory of GI and employing SWMM (Storm Water Management Model)-based stormwater modelling, we have revealed the environmental impacts at different stages of the life cycle of the GI scenario and three GIs through comparative and sensitivity analyses. Notably, we have disclosed, for the first time, the effect of the runoff coefficient in LCA. Our findings indicate that over the 30-year life cycle, the total environmental impact of the GI scenario is 24 % smaller than that of the hypothetical grey scenario. Permeable pavement exhibits the largest environmental impact per unit area, being 1.8 times and 7.6 times greater than that of the green roof and sunken green space, respectively. The operation stage of the three GIs significantly mitigates eutrophication and climate change. Furthermore, sensitivity analysis demonstrates that an increase in surface runoff undermines the environmental benefits of GIs. These results highlight the importance of embedding stormwater modelling into LCA, enabling catchment-scale integrated evaluation and equivalent assessment of different GIs within a single catchment whereby the influence of external factors such as climate change can be described, which aids in understanding the dynamic environmental performance of GIs. The proposed research framework and results are anticipated to provide valuable guidance for future GI construction and carbon-neutral policies. [Display omitted] •Life cycle assessment of green and grey scenario at catchment scale•Life cycle assessment of three typical green infrastructure in a single catchment•Stormwater modelling helps assess life cycle environmental impact.•Green scenario has 24 % lower impact; permeable pavement has largest impact per unit.•Increased runoff undermines the environmental improvement of green infrastructure.